Unilateral above-knee amputees achieve symmetric mediolateral ground reaction impulse in walking using an asymmetric gait strategy. (22nd January 2021) - Hisano, Genki; Hashizume, Satoru; Kobayashi, Toshiki; Major, Matthew J.; Nakashima, Motomu; Hobara, Hiroaki
Abstract: The ability to sustain steady straight-ahead walking is one goal of gait rehabilitation for individuals with unilateral above-knee (UAK) amputation. Despite the morphological and musculoskeletal asymmetry resulting from unilateral limb loss, the mediolateral ground-reaction-impulse (GRI) should be counterbalanced between the affected and unaffected limbs during straight-ahead walking. Therefore, we investigated the strategies of mediolateral ground-reaction-force (GRF) generation adopted by UAK prosthesis users walking along a straight path. GRFs of 15 participants with UAK amputation were measured during straight-ahead walking. Then, the mediolateral GRI, stance time, and mean mediolateral GRF during the stance phase of the affected and unaffected limbs were compared. To better understand the GRF generation strategy, statistical-parametric-mapping (SPM) was applied to assess the phase-dependent difference of the mediolateral GRFs between two limbs. The results showed that UAK prosthesis users can achieve symmetric mediolateral GRI during straight-ahead walking by adopting an asymmetric gait strategy: shorter stance time and higher mean mediolateral GRF over the stance phase for the affected than for the unaffected limb. In addition, the analysis using SPM revealed that the affected limb generates a higher mean medial GRF component than the unaffected limb, especially during the single-support phase. Thus, a higher medial GRF during the single-support phase of the affected limb may allow UAK prosthesis users to achieve mediolateral GRI that are similar to those of the unaffected limb. Further insights on these mechanics may serve as guidelines on the improved design of prosthetic devices and the rehabilitation needs of UAK prosthesis users.